INTERACTION BETWEEN NARCISSISM PERSONALITY TYPE AND SELF-REGULATION IN STUDENTS PSYCHOLOGICAL ISSUES - Alguliyev, Vusal (Health and Society, 2024)
The article is devoted to the study of the relationship between narcissism personality type and self-regulation. 150 students participated in our research. The main part of the selection is students studying at a higher education institution. The study showed that when evaluating the differences between groups with different severity of the indicator of self-regulation and self-attitude, significant differences were obtained only on two scales: lack of empathy and envy of the achievements of others. A lack of empathy and envy of others’ achievements appeared to be more common among respondents with low self-esteem, i.e., those with predominantly negative self-images. The effects of personality type and narcissistic personality traits on self-attitude factors are negative, except for grandiose self-worth and belief in one’s own uniqueness. It was found that there is a contradiction in the structure of self-attitude of a narcissistic personality: a positive self-attitude maintains an acceptable level due to greatness and belief in one’s own uniqueness and specialness, but precisely these characteristics emerge. being the basis for envy and manipulation in interpersonal relationships. Realizing that such strategies are unacceptable leads to shame and experiencing one’s own flaws. In response, the personality either focuses on the painful side of such experiences, which increases feelings of envy, leading to narcissistic outbursts of anger and submissive behavior, or strives for self-affirmation and social achievement, which helps maintain a sense of superiority.